The Relationship Between Certain Body Measurements and Passing The Asian Academy Futsal Referees' Exams - Ahmed Kazem Katea Khalifa; Mustafa Abdul Karim Mahna (Penerbit Jurnal Indonesia, 2025)
The research aims to identify the relationship between body measurements and passing the Asian Academy tests for futsal referees. It also aims to identify the body measurements that contribute most to success in those tests. The researcher used the descriptive method with a correlational approach to suit the nature of the research. The research population consists of futsal referees nominated to enter the Asian Academy, and they were selected purposively, and their number reached (13 referees). The research tools consisted of anthropometric measurements (body height, body weight, leg length, hip circumference, chest width, abdominal circumference, and arm length) in addition to the results of the physical tests approved by the Asian Academy. For statistical data analysis, the researchers used the arithmetic mean, standard deviation, and Pearson's correlation coefficient. The results showed a statistically significant correlation between some anthropometric measurements and the results of the Asian Academy futsal referee test. The researchers concluded that there is a significant correlation between the Asian Academy test and body mass index, as well as between the Asian Academy test and hip circumference. The researchers recommend adopting anthropometric measurements when selecting new referees in futsal.